Some assessment results of the medical care for newborns - Moiseeva, K. E.; Yuryev, V. K.; Alekseeva, A.V; Glushchenko, V. A.; Kharbediya, Sh. D. (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2019)
In order to assess the state of medical care for newbornsin organizations of obstetric care in 2013-2017, the officialstatistical reports of the Ministry of Healthcare of Russia andpublications of the Federal State Statistics Service were analyzed.It was found that during the study period, the provisionof neonatologists increased by 2.8%, and the provisionof beds for pathology of newborns and premature infants fellby 2.9%. The incidence of newborns born with a body weightof 1000 g and more decreased by 5.0%, and the incidenceof newborns born with extremely low body weight increasedby 14.1%. Mortality of mature and premature newborns in obstetricorganizations as a whole decreased by 43.7%. From2013 to 2017 in Russia there was a decrease in the share oflevel 1 organizations (by 5.6%) and the growth of level 2 and3 organizations (by 4.2% and 25.0%, respectively). Due to theregionalization of obstetric and perinatal care, the proportionof live births in level 1 maternity hospitals (departments) decreasedby 33.6% and 6.1% in level 2 obstetric hospitals, butincreased by 26.7% in level 3 obstetric care organizations.The same trend was observed in the distribution of newborns’deaths by levels of hospitals: in obstetric hospitals of level 1and 2 there was a decrease of 47.4% and 40.9%, respectively,in perinatal centers - an increase of 44.0%. Thus, theincrease in the level of medical care for newborns led to adecrease in the mortality of mature and premature newbornsin obstetric hospitals, but led to a simultaneous increase inmorbidity due to the nursing of newborns born with extremelylow body weight